2013
DOI: 10.1177/1098612x13488385
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous sinus syndrome due to osteochondromatosis in a cat

Abstract: A 1-year-old sexually intact male Korat cat was referred for ophthalmological consultation due to anisocoria. Mydriasis with external ophthalmoplegia and absence of pupillary light responses in the right eye and nasofacial hypalgesia were seen. Cavernous sinus syndrome (CSS) was suspected. Bilateral deformities of the jaw and phalangeal bones, severe spinal pain and abnormal conformation of the lumbar spine were also present. Radiographic examination revealed several mineralised masses in the appendicular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…Advanced cross‐sectional imaging, while not always feasible in large animals, did provide additional information, confirming the localization of the clinical signs to the cavernous sinus. By contrast, previous reports in the veterinary literature in dogs and cats have most often found that the syndrome is a result of neoplasia. However, other potential causes include infectious and noninfectious, vascular, and traumatic pathologies .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Advanced cross‐sectional imaging, while not always feasible in large animals, did provide additional information, confirming the localization of the clinical signs to the cavernous sinus. By contrast, previous reports in the veterinary literature in dogs and cats have most often found that the syndrome is a result of neoplasia. However, other potential causes include infectious and noninfectious, vascular, and traumatic pathologies .…”
Section: Discussioncontrasting
confidence: 73%
“…Cavernous sinus syndrome (CSS) has been described in dogs and cats, but to the authors' knowledge has not been described in cattle. The cavernous sinus is a paired venous structure at the base of the cranial cavity surrounding the stalk of the pituitary gland that plays a role in venous drainage for the orbit and brain .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs are associated with pain and loss of function, and malignant transformation to parosteal osteosarcoma may occur (Mozos and others 2002, Pollard and Wisner 2013). Recently, cavernous sinus syndrome due to intracranial osteochondroma was described in a cat (Perazzi and others 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Documented cases of feline and canine internal ophthalmoparesis/ophthalmoplegia are limited in the veterinary literature. Most of the literature in dogs and cats with internal ophthalmoparesis/ophthalmoplegia are case reports with middle cranial fossa syndrome (also known as cavernous sinus syndrome) . Middle cranial fossa syndrome is a clinical disorder characterized by ipsilateral internal ophthalmoparesis/ophthalmoplegia, paresis, or plegia of the extra‐ocular muscles (also known as external ophthalmoparesis/ophthalmoplegia) and decreased to absent facial and corneal sensation .…”
Section: Introductionmentioning
confidence: 99%
“…Case reports in dogs have included chondrosarcoma, lymphoma, meningioma, primitive neuroectodermal tumors, metastatic invasion of thyroid carcinomas, neuroendocrine carcinoma, and an aneurysm as the underlying cause . Reports in cats have included osteochondroma, lymphoma, squamous cell carcinoma, chondrosarcoma, trauma, orbital abscessation, and infectious diseases (feline infectious peritonitis/Cryptococcus) as the underlying cause …”
Section: Introductionmentioning
confidence: 99%